Review: Quality of Life in Children with Non-cystic Fibrosis Bronchiectasis - Nathan, Anna Marie; de Bruyne, Jessie Anne; Eg, Kah Peng; Thavagnanam, Surendran (Frontiers in Pediatrics, 2017)
Non-cystic fibrosis bronchiectasis (NCFB) has gained renewed interest, due to its increasing healthcare burden. Annual mortality statistics in England and Wales showed that under 1000 people die from bronchiectasis each year and this number is increasing by 3% yearly. Unfortunately, there is a severe lack of well powered, randomised controlled trials to guide clinicians how to manage NCFB effectively. Quality of life (QOL) measures in NCFB is an important aspect of clinical care that has not been studied well. Commonly used disease specific questionnaires in children with NCFB are the St George’s respiratory Questionnaire, Short Form-36, the Leicester Cough Questionnaire and the Paediatric Cough quality of life questionnaire(PC-QOL). Of these, only the PCQOL can be used in young children, as it is a parent-proxy questionnaire. We reviewed paediatric studies looking at QOL in children with NCFB and cystic fibrosis. All types of airway clearance techniques appear to be safe and have no significant benefit over each other. Number of exacerbations and hospitalizations correlated with QOL scores while symptoms subscales correlated with lung function, worse QOL, frequent antibiotic requirements and duration of regular follow-up, in only one study. There was a correlation between QOL and age of diagnosis in children with primary ciliary dyskinesia. Other studies have shown no relationship between QOL scores and aetiology of NCFB as well as CT changes. As for treatments, oral azithromycin and yoga have demonstrated some improvement in QOL scores. In conclusion, more studies are required to accurately determine important factors contributing to QOL.